Chloroplast ultrastructure and thylakoid polypeptide composition are affected by different salt concentrations in the halophytic plant Arthrocnemum macrostachyum - Trotta, Andrea (Journal of plant physiology, 2012)
Copyright © 2011 Elsevier GmbH. All rights reserved.